2016
DOI: 10.1097/cji.0000000000000114
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role of the Avidity of T-Cell Receptor in Differentiation of Self-Antigen-reactive CD8+ T Cells

Abstract: Many studies demonstrated crucial roles of avidity of T-cell receptor (TCR) in T-cell fate. However, majority of these findings resulted from analysis of non-self-antigen-specific CD8 T cells, and little is known about roles of TCR avidity in the fate of self-antigen-specific CD8 T cells. Wilms tumor gene 1 (WT1) protein is a self-antigen most suitable for addressing this issue because WT1 protein is a highly immunogenic, typical self-antigen. Here, we isolated 2 distinct and functional TCRs, TCR1 and TCR2, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Allen PM and his colleagues reported that the magnitude of secondary response in Listeria-specific T cells was determined by the strength of TCR functional avidity to self-antigen [ 34 , 35 ]. Furthermore, we previously demonstrated that WT1-specific CD8 + T cells with high-avidity TCR to WT1 peptide easily differentiated into effector T cells in TCR-retrogenic mice [ 36 ]. However, it remains unclear how TCR avidity controls T cell responses and their fate, especially memory/effector differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Allen PM and his colleagues reported that the magnitude of secondary response in Listeria-specific T cells was determined by the strength of TCR functional avidity to self-antigen [ 34 , 35 ]. Furthermore, we previously demonstrated that WT1-specific CD8 + T cells with high-avidity TCR to WT1 peptide easily differentiated into effector T cells in TCR-retrogenic mice [ 36 ]. However, it remains unclear how TCR avidity controls T cell responses and their fate, especially memory/effector differentiation.…”
Section: Discussionmentioning
confidence: 99%